Efficacy of post-inpatient aftercare treatments for anorexia nervosa: a systematic review of randomized controlled trials - Katrin E. Giel; Simone C. Behrens; Kathrin Schag; Peter Martus; Stephan Herpertz; Tobias Hofmann; Eva-Maria Skoda; Ulrich Voderholzer; Jörn von Wietersheim; Beate Wild; Almut Zeeck; Ulrike Schmidt; et al. (Journal of Eating Disorders, 2021)
Plain English summary Patients with a severe form of anorexia nervosa (AN) are often treated as inpatients. Many of them benefit from this acute treatment. Unfortunately, a significant number of patients experience relapse after discharge. This problem could be addressed by specific treatments directly following inpatient therapy, so called aftercare interventions, which are tailored to patients’ needs in this treatment period. This review looks at studies which have investigated the efficacy of aftercare interventions for patients with AN directly after inpatient treatment. We included any studies which compared a novel aftercare intervention to a control treatment and where patients were randomly assigned to either of these treatments, as this procedure is considered to reduce bias. We found seven studies that investigated different aftercare intervention approaches, including medication, guided self-help and psychotherapy, and three ongoing studies. Based on the very limited evidence so far, no clear recommendations can be made favoring a specific approach for post-inpatient aftercare in adult patients with AN. The review shows that it should be a priority to increase uptake of aftercare interventions and to reduce dropout rates. This could be achieved by a better tailoring of interventions to patient needs and the integration of patient perspectives in intervention design. More studies are needed to find interventions which allow patients with AN to maintain treatment gains after intensive inpatient treatment.